Level of Computer Literacy of Barangay Officials of Tandaay, Nabua, Camarines Sur: Basis for Community Extension Program - Nodado, Sophia Ann H.; Bagayawa, Micah L.; Tolosa, Kenneth Godwin A. (The Indonesian Institute of Science and Technology Research, 2024)
This study aims to determine the level of computer literacy of the barangay officials in Tandaay as the basis for a community extension program. Purposive sampling was used as a sampling technique to determine the respondents. With that, a total of 37 elected and appointed barangay officials comprised the study respondents. This study is a descriptive-correlational research that made use of a checklist questionnaire to gather the data. The frequency and percent distribution, weighted mean, order ranking method, and chi-square test of independence were used to interpret the collected data. The findings revealed that the elected and appointed barangay officials are “Somewhat Unaware” in terms of computer navigation skills and online communication skills. For Microsoft Office skills and computer troubleshooting skills, the respondents are found to be “Unaware”. For the factors affecting the respondents’ level of computer literacy, the result revealed that the respondents “Agree” that the indicators in computer navigation skills, Microsoft Office skills, online communication skills and computer troubleshooting skills affect their computer literacy, especially their willingness to learn and use the computer. Moreover, there is a significant difference between the respondent’s profile and their level of awareness in computer literacy. As an output, the researchers proposed an intervention plan to improve the computer literacy of the respondents. This intervention plan is a basic computer learning workshop designed and aligned based on the results of the survey.